2014
DOI: 10.1007/s11883-014-0408-2
|View full text |Cite
|
Sign up to set email alerts
|

Antiatherothrombotic Effects of Dipeptidyl Peptidase Inhibitors

Abstract: Atherothrombotic cardiovascular events are a leading cause of morbidity and mortality in patients with type 2 diabetes (T2D). A number of factors beyond hyperglycemia contribute to this increased risk of cardiovascular events in T2D, including elevated blood pressure, dyslipidemia, inflammation, endothelial dysfunction, and enhanced platelet activation. Importantly, most currently available antihyperglycemic treatments for T2D do not address these additional mechanisms. Indeed, we posit that this may explain w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(55 citation statements)
references
References 55 publications
2
53
0
Order By: Relevance
“…Heart sections stained with 2,3,5-triphenyltetrazolium chloride (TTC) harvested 4 days after MI revealed obvious reductions in unstained infarct areas of GLP-1(28-36)-treated hearts as compared with the scramble-or saline-treated controls ( Figure 1B). Blinded histomorphometry confirmed that pretreatment with GLP-1 (28)(29)(30)(31)(32)(33)(34)(35)(36) significantly decreased infarct size 4 days after MI as compared with scramble-and saline-treated controls (24.9% ± 2.4%, n = 7, vs. scramble: 32.5% ± 1.8%, n = 7; saline: 34.3% ± 2.8% n = 9; P < 0.05 for both) ( Figure 1C), with the effect of GLP-1 (28)(29)(30)(31)(32)(33)(34)(35)(36) treatment being comparable to that of GLP-1 (23.0% ± 1.9%, n = 13; P = NS).…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…Heart sections stained with 2,3,5-triphenyltetrazolium chloride (TTC) harvested 4 days after MI revealed obvious reductions in unstained infarct areas of GLP-1(28-36)-treated hearts as compared with the scramble-or saline-treated controls ( Figure 1B). Blinded histomorphometry confirmed that pretreatment with GLP-1 (28)(29)(30)(31)(32)(33)(34)(35)(36) significantly decreased infarct size 4 days after MI as compared with scramble-and saline-treated controls (24.9% ± 2.4%, n = 7, vs. scramble: 32.5% ± 1.8%, n = 7; saline: 34.3% ± 2.8% n = 9; P < 0.05 for both) ( Figure 1C), with the effect of GLP-1 (28)(29)(30)(31)(32)(33)(34)(35)(36) treatment being comparable to that of GLP-1 (23.0% ± 1.9%, n = 13; P = NS).…”
Section: Introductionmentioning
confidence: 69%
“…Here, we show in both ex vivo and in vivo models of ischemic injury that treatment with GLP-1 (28)(29)(30)(31)(32)(33)(34)(35)(36), a neutral endopeptidase-generated (NEPgenerated) metabolite of GLP-1, was as cardioprotective as GLP-1 and was abolished by scrambling its amino acid sequence. GLP-1 (28)(29)(30)(31)(32)(33)(34)(35)(36) enters human coronary artery endothelial cells (caECs) through macropinocytosis and acts directly on mouse and human coronary artery smooth muscle cells (caSMCs) and caECs, resulting in soluble adenylyl cyclase Adcy10-dependent (sAC-dependent) increases in cAMP, activation of protein kinase A, and cytoprotection from oxidative injury. GLP-1 (28)(29)(30)(31)(32)(33)(34)(35)(36) modulates sAC by increasing intracellular ATP levels, with accompanying cAMP accumulation lost in sAC -/cells.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations